Avances en la cuantificación de inóculo de Thecaphora frezii en muestras de suelo - Bernanrdi Lima, Nelson; Paredes, Juan Andrés; Monguillot, Joaquín Humberto; Asinari, Florencia; Rago, Alejandro Mario; Conforto, Erica Cinthia (Asociación Argentina de Fitopatólogos, 2022)
Poster